A numerucal numerical method for the restoration of the five diagonal symmetric matrices from the spectral data (International Journal of Mathematics and Physics, 2015)
In this work the possibility of restoration of real symmetrical five diagonal final matrixes using four numerically sequences is studied. Three from these four numerically sequences are interpreted as sets of eigenvalues of the considered matrix and else of two matrixes, obtained from considered matrix delet-ing some diagonal elements. The concrete formulas of construction of matrix elements using four sets of eigenvalues are obtained.